PENGARUH PENGGUNAAN MEDIA GEOGEBRA TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DI SEKOLAH DASAR - Salsabila, Wulandari; Fitri, Ayu; Harmawati, Harmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The study was intended to know the effect of geogebra media on the class v's creative thinking ability on the triangular, flat building material in the sphere. The approach in this study is quantitative with experimental kinds. The design in this research is one group prescription-posttest design. The sampling technique used is a random sampling cluster. The sample that was used was the 18-student data-collecting technique used as a test in the form of an essay question. The data analysis used are descriptive analysis techniques and inferential analysis techniques. Descriptive results came from pretest tests averaged 48.94 and posttest scores of an average of 87.67. Analysis using t-test samples shows the sig (2-tailed) < 0.05 (0,000 0.05) so that ho is declined has been accepted. It may thus be concluded that the geogebra learning media affects students' regenerative ability on the triangular, flat building matter in elementary Islamic school  At-Taubah Karawang.